Dental treatment of Down Syndrome children - Kurniaty; Mila Febriany (Makassar Dental Journal, 2020)
Down syndrome children have mental and physical limitations that have implications for dental treatment that requires modi-fication of treatment approach different with normal children and emphasis on preventive care. This case report describes behavioural management in preventive and curative in DS children. An 8-year-old female patient came with her mother to De-partment of Pediatric Dentistry at RSGM of Padjadjaran University for dental care, complained that there were cavities that disturbs food chewing. Intraoral and radiographic examination showed that several anterior and posterior teeth had caries. Behavioral management carried out during treatment includes tell-show-do, positive reinforcement and descriptive praise. It was concluded that selection of appropriate behavioral management techniques in children with DS as long as it can increase positive behavior so that quality, safe, and efficient deals are achieved.